TANGGUNG JAWAB PENAKSIR AKIBAT SALAH TAKSIR OBJEK GADAI DALAM PEMBERIAN KREDIT DI PT. PEGADAIAN (PERSERO) DENPASAR - Bromm, Jezias Dhioka; ., Adiwati; ., Marwanto (Kertha Wicara : Journal Ilmu Hukum, 2013)
Responsibilities as a result of appraiser estimating object lien on lending to PT.Pawnshop (Limited) is the title of this paper which is based on the existence of acuriosity about how far the estimator is responsible for determining guilt and obligationassessment lien on the object. In this study, empirical research methods used to analyzethe responsibilities of actuaries in pawnshops, if made an error in determining theestimate of the object pawned, estimator personally responsible for mistakes to coverlosses on the company.
Keywords: liability appraiser , appraiser responsibility, estimates, objects pawn.